Theory and methodology in vocational education - Rakhmetova, Nurziya; Sakenova, Saya; Derbissova, Mariya; Kanapyanov, Serik; Suleimenova, Kymbat (International Journal of Innovative Research and Scientific Studies, 2025)
Vocational schools focus on bridging the gap between theory and practice. The concepts of theory and practice are often discussed in debates about how to address them in the classroom, particularly as they pertain to vocational and technological learning. This research adds empirical evidence to the ongoing debate over vocational education philosophy and methodology. Starting from the heterogeneous phenomenology of the lived world, this study seeks to answer questions about the theoretical and practical experiences of supervisors, instructors, and students in vocational education concerning the teaching and learning process. Thematic analysis has been applied to the narratives of students, instructors, and supervisors gathered via qualitative interviews, with an emphasis on information pertaining to theory and practice. The findings point to both theoretical and practical experiences with a more interconnected perspective and a more typical dualistic one. A more nuanced and thorough comprehension of the concepts allows for their handling in a more integrated fashion.